Effect of fine-grained dipping interlayers on mechanical behavior of tailings using discrete element method. (July 2019) - Chen, Qinglin; Zhang, Chao; Yang, Chunhe; Ma, Changkun; Pan, Zhenkai
Abstract: Due to the presence of fine-grained interlayers (frequently called lenticles), the stability of tailings dams can deteriorate. In this study, a two-dimensional numerical model with flexible boundary was constructed, and biaxial tests were carried out for samples with interlayers at different dip angles. The influence of the interlayer inclination on the mechanical properties of tailings was analyzed. The simulation results revealed that the shear strength of tailings with interlayers decreases with the increase in the interlayer dip angle. Obvious anisotropy of shear strengths was observed due to the presence of interlayers. All the deformations of the samples with interlayers were well captured in the DEM simulations. Bulging deformations were found in the samples with interlayers at dip angles of 0°, 15° and 30°. Shear slip along the fine interlayer plane was generated in the samples with interlayers with dip angles of 45° and 60°. The principal orientation of the contact unit normal and the normal contact force aligns with the loading direction for the samples with interlayer at small dip angle (i.e., 0°). However, for the sample with interlayer at large dip angle (i.e., 60°), the principal orientation trends to the direction normal to the interlayer.